Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex](3x+1)(2x-5)=39 \\
6x^2-15x+2x-5=39 \\
6x^2-13x-5=39 \ \ \ \ \ \ \ \ \ \ |-39 \\
6x^2-13x-44=0 \\
6x^2-24x+11x-44=0 \\
6x(x-4)+11(x-4)=0 \\
(6x+11)(x-4)=0 \\
6x+11=0 \ \lor \ x-4=0 \\
6x=-11 \ \lor \ x=4 \\
x=-\frac{11}{6} \ \lor \ x=4 \\
\boxed{x=-1 \frac{5}{6} \hbox{ or } x=4}[/tex]
(3x + 1)(2x - 5) = 39
3x(2x - 5) + 1(2x - 5) = 39
3x(2x) + 3x(-5) + 1(2x) + 1(-5) = 39
6x² + (-15x) + 2x + (-5) = 39
6x² - 15x + 2x - 5 = 39
6x² - 13x - 5 = 39
- 39 - 39
6x² - 13x - 44 = 0
x = -(-13) ± √((-13)² - 4(6)(-44))
2(6)
x = 13 ± √(169 + 1056)
12
x = 13 ± √(1225)
12
x = 13 ± 35
12
x = 13 + 35 ∨ x = 13 - 35
12 12
x = 48 ∨ x = -22
12 12
x = 4 ∨ x = -1⁵/₆
The solution set us equal to {4, -1⁵/₆}.
3x(2x - 5) + 1(2x - 5) = 39
3x(2x) + 3x(-5) + 1(2x) + 1(-5) = 39
6x² + (-15x) + 2x + (-5) = 39
6x² - 15x + 2x - 5 = 39
6x² - 13x - 5 = 39
- 39 - 39
6x² - 13x - 44 = 0
x = -(-13) ± √((-13)² - 4(6)(-44))
2(6)
x = 13 ± √(169 + 1056)
12
x = 13 ± √(1225)
12
x = 13 ± 35
12
x = 13 + 35 ∨ x = 13 - 35
12 12
x = 48 ∨ x = -22
12 12
x = 4 ∨ x = -1⁵/₆
The solution set us equal to {4, -1⁵/₆}.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.